Days of those made like me: retrospective pleasure, sexual knowledge, and C. P. Cavafy’s homobiographics - Papanikolaou, D (Maney, 2013)
This essay begins with a comparison between the anonymous ‘Roman d’un inverti’ (1894/5) and Cavafy’s poem ‘Να μείνει’, and then proceeds to read C.P.Cavafy’s private notes and key erotic poems in the context of late 19th and early 20th century discourses about non-normative sexuality. During that period, and in a discursive domain dominated by sexological case studies, the deviant sexual life story was published with an aim to titillate, check, control and medicalize. In Cavafy’s texts we see, instead, a network of homosexual life-stories proposed as a platform for the conceptualization of novel sexual, aesthetic and social technologies, as well as a new ethics of contact.